Rancang Bangun Sistem Informasi TOEFL pada Pusat Bahasa Universitas Mataram - Imam Tantowi; Moh. Ali Albar; Fitri Bimantoro (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
This research was conducted based on existing problems in the registration system, scheduling, and announcement of the results of the TOEFL test at the Language Center of the University of Mataram. Where registration, scheduling, and the announcement of TOEFL test results are done manually which requires prospective participants to register directly at the language center of the University of Mataram. This system is expected to simplify the registration process, scheduling, displaying available quotas and checking TOEFL test results. This system was built using a CodeIgniter framework, XAMPP as a web server and MySQL PhpMyadmin as its database server and built with the waterfall model as a system development method. This system is tested by the black box method and user interface testing will be used subjectively testing using the mean opinion score (MOS) by involving several respondents. Based on the test results of the Mean Opinion Score method, it can be concluded that 66.1% of the respondents agreed and 33% of the respondents strongly agreed with the TOEFL Information System Design in UNRAM.